Telaah Sejarah Maritim Islam Dengan Pendekatan Leksiko-Semantik - Encep - Rustandi (IAIN Syekh Nurjati Cirebon, 2023)
Evidence of the history of the sea in Islam, can be seen from the existence of historical evidence in the form of relics and terminology that are still used in the language community, especially the Arab community. Based on this explanation, the author tries to study manuscripts on the history of the sea in Islam through a lexico-semantic approach in the form of entries from several Indonesian-Arabic and English Bilingual dictionaries, as well as manuscript descriptions of the history of the sea in Islam, inventory at the word level, and semantic analysis at the word level. and sentences. The research findings show that the text descriptions of Islamic history show that several terms refer to the fields of maritime, navy, and political icons and my which characterize Islamic maritime history, besides that several entries have experienced several changes and shifts in meaning.Â Â Â